203k views
21 votes
CAn U hElp mE pLz
∛-6x²+4x when x=−6

User Sadhana
by
4.6k points

2 Answers

12 votes
The answer is one hundred and two
User Habib Kazemi
by
4.2k points
5 votes

Answer:

102

Explanation:

to do these you need to substitute x with -6

-6(-6)² +4(-6)

solve brackets first

-6(-6*-6) + 4 * -6

= -6 (36) + (-24)

plus + minus is minus

plus * minus is minus

minus * minus is plus

= 126 - 24

= 102

User Thachnb
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.